Stress sources and symptoms: the role of gender in a Brazilian university medical school - Romeo, Marina; Marques, Antonio Luiz; Yepes-Baldó, Montserrat; Boria-Reverter, Sefa (Frontiers in Public Health, 2025)
IntroductionThe main objective of this research was to identify the sources and symptoms of occupational stress among Brazilian university professors and examine the impact of gender on this relationship.MethodsA total of 81 university professors from a Brazilian Federal University Medical School answered a questionnaire that collected demographic and occupational data, lifestyle information, health issues, and stress symptoms originating from work and personal factors. Univariate statistics, Spearman correlation and the forgotten effects theory were used to analyze the data.ResultsParticipants experienced medium-high stress levels from individual factors and low stress levels from work-related factors. Common stress symptoms included fatigue and nervousness. There was a significant correlation between stress sources from work and individual factors, with different symptoms linked to each source. Gender moderated the relationship between work-related stress sources and symptoms and the forgotten effects theory revealed overlooked but significant cause-and-effect relationships.DiscussionUniversities should implement supportive measures and policies that consider the unique challenges faced by faculty, particularly related to gender. These initiatives can create a healthier and more productive work environment for professors and benefit both faculty members and students alike.